Historical analisys and heuristics as a function of emergency team education - experience of the CMoD Zrenjanin - Bereš, Paun J.; Bereš, Kristian P.; Cvetković, Sreten S.; Jazić, Radovan M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
This paper presents a problem solving by applying a historical analysis and heuristics in order to make appropriate decisions in emergency situations and emergency with special reference to the use of heuristic models of educating teams-staff for emergencies. It is designed for command and teaching staff of the Civil Defence: local authorities (chiefs of districts, mayors and mayors-commanders) and the system of protection and rescue (Department of Emergency). A historical analysis and a heuristic approach to solving the problem is to enable the command staff from the local to the national level to make adequate decisions in emergency situations after the proclamation of emergency and a state of emergency in parts of the territory, or across the territory of the Republic of Serbia, as well as to point out the necessity of coordination between local and national levels.